Comment on "Discrete-time optimal fuzzy controller design global concept approach". - Chonghui Song
In this correspondence, we show that the relationship between the finite optimal trajectory and the infinite optimal trajectory in Lemma 3 of the aforementioned paper cannot act as a theory basis for the further implementation of other theorems and the dynamic decomposition algorithm.
Keywords: Discrete-time optimal fuzzy control; Dynamic decomposition algorithm; Finite optimal trajectory; Global concept approach; Infinite optimal trajectory